Pengaruh Pendidikan Kewirausahaan, Efikasi Diri Dan Locus Of Control Terhadap Intensi Berwirausaha - Anastasia Blegur; Sarwo Edy Handoyo (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
The purpose of this research is to determine the effect of entrepreneurship education, self-efficacy and locus of control on entrepreneurial intentions of Tarumanagara University Faculty of Economics students. This study uses a non-probability sampling method with the number of samples taken in the study were 150 respondents of the Faculty of Economics students at Tarumanagara University. This questionnaire was distributed to respondents from the Economics department who had taken entrepreneurship courses. Data analysis method uses SEM (Structural Equation Modeling) with the SmartPLS program. The results of this study indicate that there is an influence of entrepreneurship education, self efficacy and locus of control on entrepreneurial intentions of Tarumanagara University Faculty of Economics students. Tujuan penelitian ini adalah untuk mengetahui pengaruh pendidikan kewirausahaan, efikasi diri dan locus of control terhadap intensi berwirausaha mahasiswa Fakultas Ekonomi Universitas Tarumanagara. Penelitian ini menggunakan metode pengambilan sampel non-probability sampling dengan jumlah sampel yang diambil dalam penelitian ialah 150 responden mahasiswa Fakultas Ekonomi Universitas Tarumanagara. Kuesioner ini dibagikan kepada responden jurusan Ekonomi yang sudah mengambil mata kuliah kewirausahaan. Metode analisis data menggunakan SEM (Structural Equation Modelling) dengan program SmartPLS. Hasil penelitian ini menunjukan bahwa terdapat pengaruh pendidikan kewirausahaan, efikasi diri dan locus of control terhadap intensi berwirausaha mahasiswa Fakultas Ekonomi Universitas Tarumanagara.